Resource Sharing Resources during a Pandemic: A Review. Issue 3 (15th July 2021) - Hogan, Sean; Paulus, Amy R.; Hannan, Heather; Wobick, Kim
Abstract: Resource sharing professionals working in interlibrary loan, document delivery, and electronic reserves have created a plethora of reference resources available to fellow professionals since the early stages of the coronavirus pandemic in the United States, that began around mid-March 2020. We have delved through the plethora of currently available resources and offer this list of resources as example of the resource sharing community's exemplary efforts to continue doing what we do best and to stay connected, during this public health crisis.